Methodological Review: Contributing Factors on Children's Educational Achievement (Prithvi Academic Journal, 2025)
Methodological review explores the diverse methodologies employed in research. This study critically examines the research methodologies employed in studying the contributing factors on children's educational achievement. With a focus on recent advances and future directions, this review provides a comprehensive overview of the development of the field, identifies methodological strengths and limitations, and offers insights for enhancing the rigor and relevance of future research. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, this review synthesizes empirical studies published in peer-reviewed journals. By analyzing a range of studies, prominent trends and patterns in research methodologies are identified, with a focus on their implications for applicability and generalizability. Quantitative dominance, standardized testing, and diverse analytical techniques stand out as common approaches. Notably, interdisciplinary collaboration, mixed-methods designs, and longitudinal studies are on the rise. The integration of various data sources and consideration of demographic variables contribute to enriched investigations. Findings underscore the importance of employing rigorous and varied methodologies for a comprehensive understanding of this complex phenomenon. The influence of methodological choices on the external validity of research results is examined, with an emphasis on the necessity of considering cultural and contextual variations in the applicability of findings. Researchers are encouraged to adopt a balanced approach, combining quantitative and qualitative methods, to capture both numerical trends and contextual nuances in this field of study.